Inteligencia artificial para el fomento del pensamiento crítico de los estudiantes de tercero bachillerato de la unidad educativa réplica "Nicolás Infante Díaz" 2023-2024 - Ponce Rivera, Luis Gabriel (2025)
Artificial intelligence (AI) is revolutionizing the educational field by improving access to resources and enhancing the learning process. However, its misuse can negatively affect the development of critical skills. At Unidad Educativa Réplica "Nicolás Infante Díaz", third-year high school students exhibit a high dependency on artificial intelligence (AI) tools, which limits their reasoning and reflection. This research aims to design interactive workshops mediated by AI to foster critical thinking and reflective learning in students.